"Being Together" in Learning: A School Leadership Case Study Evoking the Relational Essence of Learning Design at the Australian Science and Mathematics School. Issue 1 (30th August 2019) - Bills, Andrew; Howard, Nigel
Abstract: In this report on an interview-based school case study undertaken with seven school leaders using component theory analysis and the hermeneutic method, we reveal the relational essence of learning design at the Australian Science and Mathematics School. The phenomenon of learning togetherness presents, forged by deliberately practised notions of contributive leadership within open learning spaces and ongoing attention to new interdisciplinary curriculum forms. This case study highlights the phenomenological nature of a school that has been deliberately purposed for deep collaborative learning forms, respecting student and teacher ideas in the process, and marginalising habitual industrial school design forms that constrain effective student and teacher learning. The study has relevance for school leaders and teachers wishing to pursue new school design forms within enabling learning cultures that attend more closely to the learning needs of young people poised to enter the Third and Fourth Industrial Revolutions.